A preparation method of sulfur, nitrogen and boron co-doped lithium iron phosphate
Patent Information
- Application Number
- CN202410846805.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-06-27
AI Technical Summary
[0006]本发明提供了一种硫、氮、硼共掺的磷酸铁锂的制备方法,以解决现有元素掺杂磷酸铁锂正极材料制备方法对磷酸铁锂粒径的调控、电子导电性和锂离子扩散传输均有所局限,不能进一步提高磷酸铁锂正极材料倍率性能的技术问题
[0034] 1. This invention uses inexpensive biochar as raw material, which reduces raw material cost and production cost; at the same time, biochar itself has nitrogen source and carbon source, which saves the cost of adding nitrogen source separately. After high temperature sintering, nitrogen source and carbon source will form a continuous conductive electron layer, which provides a channel for lithium ion insertion and extraction and improves its electrical performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode material technology, and more specifically, to a method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate. Background Technology
[0002] Lithium iron phosphate (LFP) is widely used in electric vehicles and energy storage due to its high theoretical specific capacity (170 mAh / g), low cost, and environmental friendliness; however, its low electronic conductivity and lithium-ion diffusion rate limit its further development. To address this issue, the main methods currently employed are carbon coating, metal and non-metal doping, and particle nanostructuring. Non-metal doping is one way to improve the intrinsic conductivity of LFP, and researchers commonly use nitrogen, phosphorus, sulfur, and boron as doping elements. Different metal elements have different effects on the performance of LFP. Therefore, researchers often use multi-element doping to modify LFP.
[0003] Existing techniques typically use traditional carbon materials such as sucrose, glucose, and rock sugar as carbon sources to coat lithium iron phosphate cathode materials. While this method improves the electronic conductivity of lithium iron phosphate cathode materials to some extent, it has limitations in controlling the particle size of lithium iron phosphate, electronic conductivity, and lithium-ion diffusion and transport. Under high-rate discharge conditions, it is prone to causing the structure of lithium iron phosphate cathode materials to collapse, which in turn leads to the problem of short cycle life in lithium-ion batteries made using this lithium iron phosphate cathode material.
[0004] For example, patent CN107359336A discloses a method for preparing lithium iron phosphate, including the following steps: a) mixing an iron source, a phosphorus source, a lithium source, and a carbon source uniformly, and calcining them under a protective atmosphere to obtain a calcined product; b) grinding the calcined product and drying it; c) calcining the dried calcined product again under a protective atmosphere to obtain lithium iron phosphate. Another example is patent CN108493424A, which discloses a nitrogen, phosphorus, and sulfur co-doped composite carbon material, its preparation method, and a lithium-ion battery. The method includes: 1) mixing a nitrogen-containing biomass carbon material, a phosphorus-doped graphene precursor, a sulfur source, and an activator, impregnating them with water, and then drying them; 2) then activating them at 600℃~1000℃ to obtain the nitrogen, phosphorus, and sulfur co-doped composite carbon material.
[0005] However, the carbon source coating method used in the above patents cannot fundamentally solve the problems of poor electronic conductivity and lithium ion diffusion in lithium iron phosphate cathode materials. It has limitations in the control of lithium iron phosphate particle size, electronic conductivity and lithium ion diffusion and transport, and cannot further improve the rate performance of lithium iron phosphate cathode materials. Summary of the Invention
[0006] This invention provides a method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate, which solves the technical problem that existing methods for preparing element-doped lithium iron phosphate cathode materials have limitations in controlling the particle size of lithium iron phosphate, electronic conductivity, and lithium-ion diffusion and transport, and cannot further improve the rate performance of lithium iron phosphate cathode materials.
[0007] The embodiments of the present invention are achieved through the following technical solutions:
[0008] A method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate includes the following steps:
[0009] S1: Activation treatment of biochar;
[0010] S2: Preparation of boron-doped carbon nanotubes;
[0011] S3: A suspension is obtained by mixing activated biomass carbon, boron-doped carbon nanotubes, iron source, phosphorus source, lithium source and sulfur source;
[0012] S4: The suspension is ball-milled, spray-dried and sintered at high temperature to obtain sulfur, nitrogen and boron co-doped lithium iron phosphate.
[0013] This technical solution uses inexpensive biochar as raw material, reducing raw material and production costs. At the same time, the biochar itself contains nitrogen and carbon sources, eliminating the cost of adding nitrogen sources separately. After high-temperature sintering, the nitrogen and carbon sources form a continuous conductive electron layer, providing a channel for lithium-ion insertion and extraction and improving its electrical performance.
[0014] This invention also grafts boron onto carbon nanotubes, which allows for more uniform doping of boron in lithium iron phosphate. In addition, the addition of carbon nanotubes can increase the conductivity of lithium iron phosphate, further enhancing its electrochemical performance, especially its high-rate performance.
[0015] The addition of nitrogen, sulfur, and boron can make the carbon coating on the surface of lithium iron phosphate more uniform, further improving the electrical performance of lithium iron phosphate.
[0016] Preferably, in step S1, phosphoric acid is added to the biochar for activation treatment.
[0017] This technical solution uses nitrogen-containing biochar such as plant straw, dead tree bark, and peanut shells as nitrogen and carbon sources, and adds phosphoric acid to activate it. Acid activation mainly affects the specific surface area, pore size, and pore volume of biochar, resulting in carbon materials with a larger BET, which provides more active sites for subsequent lithium-ion charging and discharging.
[0018] Preferably, in step S1, the mass ratio of phosphoric acid to biomass carbon is 4 to 10:1.
[0019] In order to save costs, this technical solution uses 20% dilute phosphoric acid, and the mass ratio of dilute phosphoric acid to biochar is 20-50:1; if 85% concentrated phosphoric acid is used, the mass ratio of concentrated phosphoric acid to biochar is 5-20:1.
[0020] Preferably, step S2 includes the following steps:
[0021] 1) Add 0.5g to 1.5g of carbon nanotubes to 50ml of strongly acidic solution;
[0022] 2): After stirring the strong acid solution in a water bath, filter it and wash it with deionized water until neutral. Dry the washing product to obtain carbon nanotubes (CNTs-COOH).
[0023] 3): Add 12ml to 18ml of SOCl2 to 0.5g to 1.5g of CNTs-COOH, stir in a water bath, filter under vacuum, and wash with deionized water until neutral. Dry the washing product to obtain the CNTs-COCl product.
[0024] 4): Add 8g to 12g of pentoborane dropwise to the CNTs-COCl product, stir in a water bath, filter, wash with deionized water until neutral, and dry to obtain boron-doped carbon nanotubes B-CNTs.
[0025] Using this technical solution, boron-grafted carbon nanotubes are prepared as dopants to further enhance the electrochemical performance of lithium iron phosphate, especially its high-rate performance.
[0026] Preferably, to further improve the effect of the dopant, in step 1), the strong acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.
[0027] Preferably, in step S3, based on a total suspension mass of 100 wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 8 wt%–12 wt%: 1 wt%–5 wt%: 1 wt%–1.3 wt%, with the remainder being iron, phosphorus, and lithium sources.
[0028] Preferably, in step S3, the iron source and phosphorus source are iron phosphate; the lithium source is lithium carbonate.
[0029] Preferably, in step S3, the sulfur source is at least one of ammonium thiosulfate and ammonium sulfide.
[0030] Preferably, in step S3, the lithium iron phosphate and lithium carbonate added have a lithium iron phosphate molar ratio of 1.05 to 1.1:1.
[0031] Preferably, in step S3, the solid content of the suspension slurry is 30% to 40%.
[0032] Preferably, in step S4, the spray drying temperature is 170℃~200℃; the high-temperature sintering temperature is 720℃~800℃; and the sintering time is 4h~12h.
[0033] The technical solutions of the embodiments of the present invention have at least the following advantages and beneficial effects:
[0034] 1. This invention uses inexpensive biochar as raw material, which reduces raw material cost and production cost; at the same time, biochar itself has nitrogen source and carbon source, which saves the cost of adding nitrogen source separately. After high temperature sintering, nitrogen source and carbon source will form a continuous conductive electron layer, which provides a channel for lithium ion insertion and extraction and improves its electrical performance.
[0035] 2. This invention grafts boron onto carbon nanotubes, which allows for more uniform doping of boron in lithium iron phosphate. In addition, the addition of carbon nanotubes can increase the conductivity of lithium iron phosphate, further enhancing its electrochemical performance, especially its high-rate performance.
[0036] 3. The carbon nanotubes of this invention can improve the cycling stability at high rates. The carbon nanotubes have high electrical conductivity and can form a three-dimensional conductive network structure between lithium iron phosphate particles, which facilitates the transport of electrons and lithium ions, reduces the impedance of lithium iron phosphate, and improves the rate performance of lithium iron phosphate.
[0037] 4. The addition of nitrogen, sulfur, and boron in this invention can make the carbon coating on the surface of lithium iron phosphate more uniform, thereby further improving the electrical performance of lithium iron phosphate. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0039] Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.
[0040] Example 1
[0041] A method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate includes the following steps:
[0042] S1: Activate the biochar; add phosphoric acid to the biochar for activation, wherein the phosphoric acid is a 20% dilute phosphoric acid and the mass ratio of dilute phosphoric acid to the biochar is 35:1;
[0043] S2: Preparation of boron-doped carbon nanotubes;
[0044] 1): Add 1g of carbon nanotubes to 50ml of a strong acid solution, wherein the strong acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1;
[0045] 2): For a strong acid solution, stir for 2 hours at a water bath temperature of 80℃~90℃, filter and wash with deionized water until neutral, place the washing product in an 80℃ oven and dry for 20 hours to obtain carbon nanotubes CNTs-COOH.
[0046] 3): Add 15ml SOCl2 to 1g CNTs-COOH, stir the mixture in a water bath at 50℃~70℃ for 2h, filter the solution and wash it with deionized water until neutral, put the washing product into a vacuum drying oven at 60℃ and dry it for 20h to obtain CNTs-COCl product.
[0047] 4): 10g of pentoborane was added dropwise to the CNTs-COCl product. The mixture was stirred for 4 hours in a water bath at a temperature of 70℃~90℃. The solution was filtered and washed with deionized water until neutral. The product was placed in a vacuum drying oven and dried at 100℃ for 12 hours to obtain boron-doped carbon nanotubes B-CNTs.
[0048] S3: A suspension is prepared by mixing activated biomass carbon, boron-doped carbon nanotubes, an iron source, a phosphorus source, a lithium source, and a sulfur source. The total mass of the suspension is 100 wt%, and the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 10 wt%: 3 wt%: 1.15 wt%, with the remainder being iron phosphate and lithium carbonate. The molar ratio of the added iron phosphate to lithium carbonate is 1.075:1. The sulfur source is a mixture of ammonium thiosulfate and ammonium sulfide.
[0049] S4: The suspension is ball-milled, spray-dried, and sintered at high temperature to obtain sulfur, nitrogen, and boron co-doped lithium iron phosphate; the spray-drying temperature is 185℃; the high-temperature sintering temperature is 760℃, and the sintering time is 8h;
[0050] S5: Preparation of Lithium Iron Phosphate Cathode Material
[0051] The sulfur-, nitrogen-, and boron-doped lithium iron phosphate prepared above, along with conductive carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone, were uniformly mixed to form an electrode slurry. After coating, cutting, and vacuum drying, the slurry was assembled into a button cell for electrochemical performance testing.
[0052] The test used constant current charge-discharge, with the following parameters set: current density 50 mAg, 10 cycles; current density 100 mA / g, 10 cycles; current density 200 mAg, 10 cycles; current density 500 mAg, 10 cycles; current density 1000 mA / g, 10 cycles; current density 50 mAg, 10 cycles. The test voltage ranged from 2.0 to 3.75 V, and the scan rate was 0.1 mV / s.
[0053] In this embodiment, the initial discharge specific capacity at 0.1C rate is 163 mAh / g, the charge-discharge efficiency is 98.5%, the discharge specific capacity at 8C rate is 150 mAh / g, and the capacity retention rate after 200 cycles is 98.8%.
[0054] Example 2
[0055] The only difference between this embodiment and Embodiment 1 is that, in this embodiment, based on a total suspension mass of 100wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 12wt%: 5wt%: 1.3wt%, with the remainder being iron phosphate and lithium carbonate; the lithium iron phosphate molar ratio of the added iron phosphate and lithium carbonate is 1.075:1.
[0056] In this embodiment, the initial discharge specific capacity at 0.1C rate is 164 mAh / g, the charge-discharge efficiency is 98.4%, the discharge specific capacity at 8C rate is 152 mAh / g, and the capacity retention rate after 200 cycles is 98.2%.
[0057] Example 3
[0058] The only difference between this embodiment and Embodiment 1 is that, in this embodiment, based on a total suspension mass of 100wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 8wt%:1wt%:1wt%, with the remainder being iron phosphate and lithium carbonate; the lithium iron molar ratio of the added iron phosphate and lithium carbonate is 1.075:1.
[0059] In this embodiment, the initial discharge specific capacity at 0.1C rate is 160mAh / g, the charge-discharge efficiency is 98.3%, the discharge specific capacity at 8C rate is 148mAh / g, and the capacity retention rate after 200 cycles is 98.5%.
[0060] Example 4
[0061] The only difference between this embodiment and Embodiment 1 is that, in this embodiment, based on a total suspension mass of 100wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 12wt%:1wt%:1.3wt%, with the remainder being iron phosphate and lithium carbonate; the lithium iron molar ratio of the added iron phosphate and lithium carbonate is 1.075:1.
[0062] In this embodiment, the initial discharge specific capacity at 0.1C rate is 164 mAh / g, the charge-discharge efficiency is 98.4%, the discharge specific capacity at 8C rate is 147 mAh / g, and the capacity retention rate after 200 cycles is 95.2%.
[0063] Example 5
[0064] The only difference between this embodiment and Embodiment 1 is that, in this embodiment, based on a total suspension mass of 100wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 8wt%:5wt%:1wt%, with the remainder being iron phosphate and lithium carbonate; the lithium iron molar ratio of the added iron phosphate and lithium carbonate is 1.075:1.
[0065] In this embodiment, the initial discharge specific capacity at 0.1C rate is 161mAh / g, the charge-discharge efficiency is 97.8%, the discharge specific capacity at 8C rate is 151mAh / g, and the capacity retention rate after 200 cycles is 98.5%.
[0066] Example 6
[0067] The only difference between this embodiment and Embodiment 1 is that, in this embodiment, based on a total suspension mass of 100wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 10wt%:3wt%:1.15wt%, with the remainder being iron phosphate and lithium carbonate; the lithium iron molar ratio of the added iron phosphate and lithium carbonate is 1.05:1.
[0068] In this embodiment, the initial discharge specific capacity at 0.1C rate is 162 mAh / g, the charge-discharge efficiency is 98.1%, the discharge specific capacity at 8C rate is 151 mAh / g, and the capacity retention rate after 200 cycles is 98.3%.
[0069] Example 7
[0070] The only difference between this embodiment and Embodiment 1 is that, in this embodiment, based on a total suspension mass of 100wt%, the mass ratio of the activated biomass carbon, boron-doped carbon nanotubes, and sulfur source is 10wt%:3wt%:1.15wt%, with the remainder being iron phosphate and lithium carbonate; the lithium iron phosphate molar ratio of the added iron phosphate and lithium carbonate is 1.1:1.
[0071] In this embodiment, the initial discharge specific capacity at 0.1C rate is 161mAh / g, the charge-discharge efficiency is 98.6%, the discharge specific capacity at 8C rate is 151mAh / g, and the capacity retention rate after 200 cycles is 98.7%.
[0072] Comparative Example 1
[0073] The only difference between this comparative example and Example 1 is that in this comparative example, the biochar is added directly without phosphoric acid activation, and then activated again during subsequent high-temperature sintering.
[0074] In this comparative example, the initial discharge specific capacity at 0.1C rate is 148 mAh / g, the charge-discharge efficiency is 98%, the discharge specific capacity at 8C rate is 139 mAh / g, and the capacity retention rate after 200 cycles is 97.5%.
[0075] Comparative Example 2
[0076] The only difference between this comparative example and Example 1 is that, in this comparative example, the pentylborane is not grafted through carbon nanotubes, but is added directly along with the biochar activated by phosphoric acid.
[0077] In this comparative example, the initial discharge specific capacity at 0.1C rate is 158 mAh / g, the charge-discharge efficiency is 97.5%, the discharge specific capacity at 8C rate is 147 mAh / g, and the capacity retention rate after 200 cycles is 98.2%.
[0078] Table 1 shows the relevant data from Examples 1-7:
[0079] Table 1. Doping-related addition amounts and electrochemical performance of Examples 1-7
[0080]
[0081] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate, characterized in that: Includes the following steps: S1: Biochar is activated by adding phosphoric acid; the biochar is nitrogen-containing biochar. S2: The preparation of boron-doped carbon nanotubes includes the following steps: 1): Add 0.5g to 1.5g of carbon nanotubes to 50ml of strongly acidic solution; 2): After stirring the strongly acidic solution in a water bath, filter it and wash it with deionized water until neutral. Dry the washing product to obtain carbon oxide nanotubes. 3): Add 12ml to 18ml of SOCl2 to 0.5g to 1.5g of carbon dioxide nanotubes, stir in a water bath, filter and wash with deionized water until neutral, and dry the washing product to obtain CNTs-COCl product. 4): Add 8g to 12g of pentoborane dropwise to the CNTs-COCl product, stir in a water bath, filter, wash with deionized water until neutral, and dry to obtain boron-doped carbon nanotubes. S3: The activated biochar, boron-doped carbon nanotubes, iron source, phosphorus source, lithium source and sulfur source are mixed to obtain a suspension; based on the total mass of the suspension of 100wt%, the mass ratio of the activated biochar, boron-doped carbon nanotubes and sulfur source is 8wt%~12wt%: 1wt%~5wt%: 1wt%~1.3wt%, with the balance being iron source, phosphorus source and lithium source; S4: The suspension is ball-milled, spray-dried and sintered at high temperature to obtain sulfur, nitrogen and boron co-doped lithium iron phosphate. The high temperature sintering temperature is 720℃~800℃.
2. The method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate according to claim 1, characterized in that: In step S1, the mass ratio of phosphoric acid to biochar is 4 to 10:
1.
3. The method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate according to claim 1, characterized in that: In step 1), the strong acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:
1.
4. A method for preparing sulfur-, nitrogen-, and boron-coated lithium iron phosphate according to any one of claims 1-3, characterized in that: In step S3, the iron source and phosphorus source are iron phosphate; the lithium source is lithium carbonate.
5. The method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate according to claim 4, characterized in that: In step S3, the lithium iron phosphate and lithium carbonate added have a lithium iron phosphate molar ratio of 1.05 to 1.1:
1.
6. A method for preparing sulfur, nitrogen, and boron co-doped lithium iron phosphate according to any one of claims 1-3, characterized in that: In step S3, the solid content of the suspension is 30% to 40%.
7. A method for preparing sulfur-, nitrogen-, and boron-coated lithium iron phosphate according to any one of claims 1-3, characterized in that: In step S4, the spray drying temperature is 170℃~200℃, and the high-temperature sintering time is 4h~12h.
Citation Information
Patent Citations
Preparation method of lithium iron phosphate, lithium iron phosphate and lithium ion battery
CN107359336A
Nitrogen-phosphorus-sulfur co-doping composite carbon material, preparation method of composite carbon material and lithium ion battery
CN108493424A
Nitrogen-doped carbon modified lithium iron phosphate positive electrode material
CN115133010A